Trials, lustration, and clean elections: the uneven effects of transitional justice mechanisms on electoral manipulation. Issue 6 (19th September 2017) - Greenstein, Claire; Harvey, Cole J.
ABSTRACT: Transitional justice aims to promote democratization, but previous research has found that it has mixed effects. We address this puzzle by focussing on how transitional justice affects a necessary condition for democracy: clean elections. We test for the effects of four transitional justice mechanisms – truth commissions, lustration policies, amnesties, and trials – on two different types of electoral manipulation, using data from 187 post-transition elections held in 63 countries around the world from 1980 to 2004. We find that post-transition trials limit illegal forms of electoral manipulation, such as vote-buying and falsification of results, but have no effect on legal forms of manipulation. By contrast, lustration policies limit legal manipulation tactics, like intimidation and harassment of opponents by the security services, but do not affect illegal tactics. By showing that different aspects of transitional justice can have varying influence on electoral integrity, this project improves understanding of the mechanisms that link transitional justice and democratization.